HIV and the gut microbiome: future research hotspots and trends - Wu, Zhen; Xie, Zhan-Peng; Cui, Xin-Xin; Sun, Xiang-Bin; Zhao, Fang-Yi; Wang, Nuo; Li, Yu; Wang, Haixia; Zhang, Li; Shen, Jing; Chen, Fulei; Sun, Haogang; et al. (Frontiers in Microbiology, 2025)
BackgroundThe use of highly active antiretroviral therapy has transformed AIDS into a chronic infectious disease, but issues of chronic inflammation and immune system activation persist. Modulating the gut microbiome of patients may improve this situation, yet the specific association mechanisms between HIV and the gut microbiome remain unclear. This study aims to explore the research hotspots and trends of the HIV and the gut microbiome, providing direction for future research.MethodsWe conducted a search of the Web of Science Core Collection database up to April 30, 2024 to retrieve articles related to the relationship between the HIV and the gut microbiome. The scientific achievements and research frontiers in this field were analyzed using CiteSpace, VOSviewer, and Bibliometrix statistical software.ResultsAs of April 30, 2024, a total of 379 articles met the inclusion criteria. The number of publications in this field peaked in 2023, and the number of articles published after 2020 declined. The country with the highest number of publications was the United States (184 articles), and the institution with the most publications was the University of Colorado (USA) (21 articles). The author with the most publications was Routy Jean-Pierre (Canada) (14 articles). High-frequency keywords, aside from the key terms, included “HIV,” “inflammation,” “immune activation,” “gut microbiota,” and “translocation.” Keyword burst results indicated that short-chain fatty acids, T cells and obesity might become the focus of future research.ConclusionThe research hotspots in this field should prioritize examining the role of the primary gut microbiome metabolite, short-chain fatty acids, in reducing immune system activation and inflammation. Another emerging area of interest could be the investigation into the annual increase in obesity rates within this field. Furthermore, understanding the metabolic mechanisms of short-chain fatty acids in T cells is essential. Additionally, multi-omics analysis holds potential.